Evolution of Blood Pressure and Proteinuria in the Postpartum Period in Women with Gestational Hypertension or Pre-Eclampsia in Cotonou - ABOUBAKAR, MOUFALILOU; DANGBEMEY, D. Patrice; TOGNIFODE, Véronique; OGOUDJOBI, OGOURINDÉ MATHIEU; TSHABU TSHINGUTA ÉPSE AGUEMON, CHRISTIANE (My University, 2021)
Objective: Monitoring the evolution of postpartum blood pressure by conventional and ambulatory measurement of blood pressure on the one hand and proteinuria on the other hand in women who presented with gravidic hypertension and/or pre-eclampsia in two (02) university maternity hospitals of Cotonou (Benin). Materials and methods: This was a prospective cohort study with a descriptive aim conducted over a period of six (06) months from May 1 to October 31, 2020. Pregnant women and parturients who presented with gravidic hypertension or pre-eclampsia in two university maternity hospitals were included. Blood pressure and proteinuria had been measured on the fifteenth, thirtieth, and forty-second postpartum days. An ambulatory blood pressure measurement was also performed in those in whom blood pressure remained elevated on day 42 of postpartum. Results: The incidence of gestational hypertension and pre-eclampsia was 22.56%. The mean age of the patients was 28.96 ± 1.46 years and pregnant women aged between 20 and 30 years were the most affected by the two hypertensive disorders of pregnancy (55.7%). Blood pressure remained elevated at ambulatory measurement in 34% of cases (18/52) and significant proteinuria was found in 32.7% of cases (17/52) on day 42 of postpartumrrhea. Conclusion: Monitoring blood pressure and proteinuria during postpartum in women with hypertensive disorders of pregnancy is necessary for the follow-up. Ambulatory blood pressure measurement is a tool to refine the diagnosis. Its use in this indication should be promoted.
Keywords: Blood pressure; Proteinuria; Postpartum; Ambulatory blood pressure measurement; Cotonou